2021
DOI: 10.1128/mbio.00751-21
|View full text |Cite
|
Sign up to set email alerts
|

Host Species and Geography Differentiate Honeybee Gut Bacterial Communities by Changing the Relative Contribution of Community Assembly Processes

Abstract: Honeybees provide crucial pollination services and valuable apiarian products. The symbiotic intestinal communities facilitate honeybee health and fitness by promoting nutrient assimilation, detoxifying toxins, and resisting pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 58 publications
9
30
0
Order By: Relevance
“…This partly explains why the fungal networks from Capniidae species exhibited more interconnection compared to other stonefly families. In congruence with recent work that revealed the effect of geographic variables on ecological processes 33 , our results also find a significant link between fungal community assembly and environmental factors such as altitude, latitude, longitude, AMT, and AP. Thus, the strength of ecological processes driving fungal communities towards either divergence or convergence is dependent on environmental factors and associated evolutionary history.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This partly explains why the fungal networks from Capniidae species exhibited more interconnection compared to other stonefly families. In congruence with recent work that revealed the effect of geographic variables on ecological processes 33 , our results also find a significant link between fungal community assembly and environmental factors such as altitude, latitude, longitude, AMT, and AP. Thus, the strength of ecological processes driving fungal communities towards either divergence or convergence is dependent on environmental factors and associated evolutionary history.…”
Section: Discussionsupporting
confidence: 92%
“…Variable selection may result in the microbiota communities diversifying among distinct environmental conditions, whereas drift disperses communities 7 , 36 , 53 . Drift was the main stochastic process driving stonefly fungal communities in our study, a similar result to reports on bacterial communities in the honeybee 33 . The core fungal genus Aspergillus found in the wild stoneflies in our work has also been detected in other insects 39 , 40 , and some of its members are also found in the surrounding environment to the host, such as in the air, soil, and on plants 54 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But, it is still unclear whether, and how, REO NPs affect gut microbiota of honeybees, specifically the model species Apis mellifera . Honeybee gut microbiota could be influenced by various factors, including pathogens, antibiotics, pesticides, diet, and host attributes and environmental conditions ( Cox-Foster et al, 2007 ; Raymann et al, 2017 ; Liu et al, 2019 ; Ge et al, 2021 ). Previous study has demonstrated that the shifts of gut bacterial communities in bumblebees may serve as a characteristic of disease states, featuring as low abundance of core species and high incidence of opportunistic environmental bacteria ( Cariveau et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbial composition of honeybees is simpler than that of humans ( Kwong and Moran 2016 ). The honeybee gut harbors a diverse microbial community, among which lactic acid bacteria (LAB) and bifidobacteria are beneficial in the intestine ( Ge et al 2021 ). On the contrast, some pathogenic bacteria such as Paenibacillus larvae and Melissococcus pluton have been found to cause diseases in honeybees ( Fünfhaus et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%